Concurrent cavitary pulmonary tuberculosis and COVID-19 pneumonia with in vitro immune cell anergy - Musso, Maria (Infection, 2021)
Tuberculosis (TB) is top infectious disease killer caused by a single organism responsible for 1.5 million deaths in 2018. Both COVID-19 and the pandemic response are risking to affect control measures for TB and continuity of essential services for people affected by this infection in western countries and even more in developing countries. Knowledge about concomitant pulmonary TB and COVID-19 is extremely limited. The double burden of these two diseases can have devastating effects. Here, we describe from both the clinical and the immunological point of view a case of a patient with in vitro immune cell anergy affected by bilateral cavitary pulmonary TB and subsequent COVID-19-associated pneumonia with a worst outcome. COVID-19 can be a precipitating factor in TB respiratory failure and, during ongoing SARS-COV-2 pandemic, clinicians must be aware of this possible co-infection in differential diagnosis of patients with active TB and new or worsening chest imaging.